THE ROLE OF ENVIRONMENTAL FACTORS AND TREE INJURIES IN SOIL CARBON RESPIRATION RESPONSE TO FIRE AND FUELS TREATMENTS IN PINE PLANTATIONS - Kobziar L.N. (My University, 2007)
The need to understand how forest management practices affect soil CO2 exchange with the atmosphere (soil respiration) has increased with the recognition of a likely feedback effect of climate warming on soil respiration rates. Previous research addressing the mechanisms driving soil respiration has yielded inconsistent and/or conflicting results. This study looked to alternative above-ground forest characteristics to help explain spatial variability in soil respiration in a 30-year-old Sierra Nevada pine plantation. Fire hazard mitigation is one of the predominant management goals in these and other western US forests. Therefore, this analysis examined how fuels treatments, including shredding of understory vegetation (mastication), prescribed fire, and a combination thereof, affected soil respiration and its relationship to environmental factors and post-fire tree injuries. Multiple regression models indicated that mastication had no significant impact on soil respiration, but the roles of soil temperature and forest floor depth (O horizons) in the models increased after the treatment. Burning reduced soil respiration by ~14%, and increased its sensitivity to tree proximity and the exposure of bare mineral soil. Scorch height in burned stands was negatively correlated with soil respiration. Models incorporating only tree injury or tree proximity parameters explained between 63% and 91% of the variability in burned plantations. This work suggests that measures of above-ground forest features can increase understanding of management impacts on soil respiration, and the mechanisms by which these impacts occur. These results are especially applicable in Mediterranean climates, where moisture stress reduces the effectiveness of soil microclimate in explaining soil respiration.
Keywords: SOIL CO2 EFFLUX; PRESCRIBED BURNING; THINNING; SOIL MOISTURE; SCORCH HEIGHT